CONTENT ANALYSIS OF ABU UBAIDAH’S SPEECH ON ALJAZEERAMUBASHER’S INSTAGRAM DURING OPERATION AL-AQSA TEMPEST - Ilya Husna; Sefriyono Sefriyono; Zulfis Zulfis; Rezkiya Afril; Nabil Ahmed Banonah (Arabic Literature Department, 2024)
Abu Ubaidah's speech aired by aljazeeramubasher's Instagram account was in the spotlight after the occurrence of Toufan al-Aqsa on October 7, 2023. The firm and straightforward style of language and the use of fushah Arabic are definitely a special attraction for listeners. This study aims to describe the style of language and messages conveyed by Abu Ubaidah in his speech using the content analysis method approach of Krippendorff's perspective. The stages of Krippendorff content analysis consist of unitizing, sampling, recording, reducing, inferring, narating, and desingning. This stage is carried out with watching, listening, and note-taking techniques. The results showed that the Arabic uslub used by Abu Ubaidah was fushah Arabic in accordance with the rules of good and correct Arabic. No Abu Ubaidah used 'ammiyah Arabic at all in his speeches. Meanwhile, in terms of the message conveyed by Abu Ubaidah with Krippendorf content analysis techniques, it was found that there was an invitation and expression of optimism from Abu Ubaidah to especially Muslims and all people in the world for Allah's help to the Palestinian people and the struggle of Hamas forces in defending Palestinian land. Abu Ubaidah as the spokesman for the Izzuddin Al-Qassam brigade managed to transfer this confidence to all the audience who watched and listened to his speech.